Conflict Management on Team Performance in Hospitals - Jayusman, Iqbal Sadjali; Nasrullah, Nasrullah; Lina, Lina (Asosiasi Dosen Muda Indonesia, 2025)
The purpose of this literature review is to identify Conflict Management factors on Team performance and conflict management solutions in the nursing workplace, and the variables that influence the success of conflict resolution. The results of the study indicate that conflict in the workplace is often caused by differences in interests, ineffective communication, and high work pressure. However, with the implementation of appropriate conflict management strategies, such as open communication, fair mediation, and strengthening a collaborative work culture, conflict can be transformed into an opportunity to improve team dynamics and innovation. Good conflict management also contributes to creating a more harmonious work environment, increasing job satisfaction, and strengthening employee loyalty to the organization.